The impact of organizational culture on job satisfaction and employee engagement in the Greek energy sector - Gkania, Paraskevi; Markaki, Evangelia (International Conference on Business and Economics - Hellenic Open University, 2025)
The aim of the current dissertation was to examine the impact of organizational culture on job satisfaction and employee engagement in the Greek energy sector. For that purpose, questionnaires were handed out in Greece, employing a digital platform such as Google forms. The analysis of the data was conducted with SPSS. It included correlations and regression analyses as well as parametric tests. The results indicated that organizational culture is positively associated with job satisfaction. In other words, a positive and supportive culture leads to higher levels of job satisfaction. In this context, companies should adopt more aspects of people-oriented cultures (clan and adhocracy) for improving more the job satisfaction levels of its personnel. The most important culture aspects that drive job satisfaction i were: systematic search for new products/services, transparency in decision making units, accessibility to top leadership and supervisors concerns about employees’ personal problems. In the same length, the analysis indicated that organizational culture leads to higher levels of employee engagement. In other words, there is a positive association between culture and engagement of the staff. In this case, the most important factors of organizational culture that lead to employee engagement were: teamwork and collaboration among the staff, freedom at work, and accessibility to leadership. It is indicative that the ties between culture and engagement were stronger that the ties between culture and satisfaction from work. Overall, the research showed that a supportive organizational culture is a key determinant of job satisfaction and employee engagement. In this context, we should move towards more people-oriented culture schemes (clan and adhocracy). This will improve substantially its overall performance in the competitive landscape of the Greek energy sector. JEL Classifications: L0, L20, L29 Keywords: Organizational culture, Job Satisfaction, Employee Engagement, statistics